PERFORMANCE MONITORING AND EVALUATION MODEL OF RAJABHAT UNIVERSITIES - Sawangboon, Tatsirin; Srisa-ard, Boonchoom (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2019)
Rajabhat Universities are the university group which aimed to provide academic and high professional education for local development. The quality control of the performance of Rajabhat Universities has been defined in the Rajabhat University Act, which included the determination of performance monitoring and evaluation of Rajabhat Universities. However, the patterns of such evaluation were not clear, and they were different for each university. In this article, performance monitoring and evaluation model of Rajabhat Universities were introduced as the guideline for Rajabhat Universities to apply appropriately within each university context. The model composed of 5 elements which were 1) the evaluation of the university’s performance in implementing strategic plans which would lead to the practices under Balanced Scorecard, 2) the evaluation of the university operation based on stakeholders’ opinions considered from both internal and external stakeholders, 3)the evaluation of university websites, 4)the evaluation of the Demonstration School under Rajabhat University and 5) real-time performance monitoring and evaluation.